2022
DOI: 10.1021/jacs.2c01323
|View full text |Cite
|
Sign up to set email alerts
|

Self-Amplifying Assembly of Peptides in Macrophages for Enhanced Inflammatory Treatment

Abstract: Enzyme-regulated in situ self-assembly of peptides represents one versatile strategy in the creation of theranostic agents, which, however, is limited by the strong dependence on enzyme overexpression. Herein, we reported the self-amplifying assembly of peptides precisely in macrophages associated with enzyme expression for improving the anti-inflammatory efficacy of conventional drugs. The self-amplifying assembling system was created via coassembling an enzyme-responsive peptide with its derivative functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Although circumscribed inflammation is beneficial for human health, excessive or persistent inflammation causes allergies, autoimmune diseases, asthma, and sepsis, which are the major causes of illness and death. IEISAP has been implemented to improve the efficacy of a traditional antiinflammatory drug dexamethasone (DEX) by increasing its cellular uptake and retention and prolonging drug release [ 120 ], or decreasing its ROS-caused side effects [ 121 ]. For example, Song et al reported the self-amplifying assembly of peptides in response to the expression of the enzyme NAD(P)H quinone dehydrogenase 1 (NQO1) in inflamed macrophages for improving the efficacy of DEX ( Figure 9 ) [ 121 ].…”
Section: Disease Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although circumscribed inflammation is beneficial for human health, excessive or persistent inflammation causes allergies, autoimmune diseases, asthma, and sepsis, which are the major causes of illness and death. IEISAP has been implemented to improve the efficacy of a traditional antiinflammatory drug dexamethasone (DEX) by increasing its cellular uptake and retention and prolonging drug release [ 120 ], or decreasing its ROS-caused side effects [ 121 ]. For example, Song et al reported the self-amplifying assembly of peptides in response to the expression of the enzyme NAD(P)H quinone dehydrogenase 1 (NQO1) in inflamed macrophages for improving the efficacy of DEX ( Figure 9 ) [ 121 ].…”
Section: Disease Treatmentsmentioning
confidence: 99%
“…IEISAP has been implemented to improve the efficacy of a traditional antiinflammatory drug dexamethasone (DEX) by increasing its cellular uptake and retention and prolonging drug release [ 120 ], or decreasing its ROS-caused side effects [ 121 ]. For example, Song et al reported the self-amplifying assembly of peptides in response to the expression of the enzyme NAD(P)H quinone dehydrogenase 1 (NQO1) in inflamed macrophages for improving the efficacy of DEX ( Figure 9 ) [ 121 ]. The authors coassembled a quinone propionic acid (QPA)-linked pentapeptide AmpFQ and its derivative (AmpFQ−ETGE), containing an ETGE sequence from the nuclear factor erythroid 2-related factor 2 (Nrf2) domain, leading to the formation of AmpFQB nanoparticles.…”
Section: Disease Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural and spontaneous self-organized amyloid fibril assemblies have encouraged the study of peptides as bio-supramolecular structural building blocks [ 1 , 2 , 3 ]. The behavior of peptides, which can self-assemble into various nanostructures, has attracted much attention because of their applications in biomedical, bioengineering and drug production [ 4 , 5 , 6 , 7 , 8 ]. In contrast to other supramolecular structural motifs, the unique and desirable features of peptides include their chemical diversity, sequence-specific secondary structures, biomolecular recognition, high biocompatibility, and ease of synthesis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by nature, many artificial self-assembled peptide-based materials have been developed in recent years. , Morphology modulation of peptide-based self-assembly under specific conditions has been emerging as a versatile strategy in controlling cellular behaviors . One of the most commonly used methods for controlling self-assembly is to utilize the selective catalytic activity of biomarkers (e.g., enzyme, pH, and temperature). Ideally, the designed peptides should respond to subtle changes in the physiological conditions of the targeted physiological conditions. Yet, such endogenous-dependent strategies are usually limited to physiological conditions where there is a significant difference between normal and tumor tissue.…”
mentioning
confidence: 99%